PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MOTIVASI BELAJAR SISWA XI IPS4 MATA PELAJARAN EKONOMI - Kardila, Ika; Aminuyati, Aminuyati; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine whether there is an influence and how much its influence the pedagogic competence of teachers to the motivation to learn Xi Ips4 Class Students on Economics Subjects at SMAN 01 Sungai Raya in Academic Year 2018/2019 which amounted to 34 students. The method used is descriptive method. Data collected with questionnaires that have been tested validity of its reliability. The data analysis technique used is SPSS program version 17.0. the results of this study showed that after doing a simple linear regression test on the variables X and Y said that the pedagogic competence of teachers have a positive effect on students' learning motivation with the regression equation Y = 27.424 + 0.609X and has an influence of 25%. By doing hypothesis test compare significant value with 0,05, while obtained significant value equal to 0,03 <0,05 so it can be concluded that (Ha) accepted (H0) is rejected, then do hypothesis test compare value t arithmetic with t table obtained t count is 3.268> 16938 t table so that (H0) is rejected and (Ha) is accepted which means there is influence between